(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to analyze the tax impact of financial crises on the proceeds of tax income. The research problem is that the tax performance in the current reality of financial crises has a role in the tax proceeds? The research shows the concept of financial crises, characteristics and species, the focus on the causes of their occurrence and the impact of financial crises. (ISIS Terrorist Organization Crisis, Low Oil Prices, Covid-19 Coronavirus Pandemic Crisis) On tax performance and revenues derived from the General Tax Authority and highlighting the role of tax performance in increasing tax yields if the methodology is adopted in theory based on literature and some previous studies as well as the analytical descriptive approach because it is an appropriate methodology for research and studies and obtaining the necessary data from its main sources. The annual financial statements of the General Tax Authority are selected and the instruments adopted in the analysis of public data and financial lists are based on ratios 2014 The researcher has a number of conclusions, the most important of which are: The crises that Iraq experienced during the period of the 2014-2021 study have had a negative impact on the tax yield and on the efficiency and effectiveness of Iraq’s tax performance. The researcher also made a number of recommendations, the most important of which are: activating and increasing the efficiency of Iraq’s tax system during crises and predicting, managing and planning risks to avoid the negative effects that may occur.